2018
DOI: 10.1002/jbm.a.36530
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyogenic differentiation of human bone marrow‐derived mesenchymal stem cell spheroids within electrospun collagen nanofiber mats

Abstract: Collagen is the major structural protein in myocardium and contributes to tissue strength and integrity, cellular orientation, and cell–cell and cell‐matrix interactions. Significant post‐myocardial infarction related loss of cardiomyocytes and cardiac tissue, and their subsequent replacement with fibrous scar tissue, negatively impacts endogenous tissue repair and regeneration capabilities. To overcome such limitations, tissue engineers are working toward developing a 3D cardiac patch which not only mimics th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 49 publications
(144 reference statements)
0
24
0
Order By: Relevance
“…In another study, Li et al investigated the cardiomyocyte differentiation potential of the human iPSCs while cultured on the multi‐layered poly(D,L‐lactic‐co‐glycolic acid) nanofibers, and their results demonstrated that this scaffold could be considered as a potential framework for cardiac tissue engineering 31 . Increase in cardiomyocyte differentiation potential of embryonic stem cells (ESCs) cultured on PLGA‐collagen nanofibers and MSCs cultured on collagen nanofibers was reported previously by Prabhakaran et al 32 and Joshi et al, 33 respectively.…”
Section: Discussionmentioning
confidence: 80%
“…In another study, Li et al investigated the cardiomyocyte differentiation potential of the human iPSCs while cultured on the multi‐layered poly(D,L‐lactic‐co‐glycolic acid) nanofibers, and their results demonstrated that this scaffold could be considered as a potential framework for cardiac tissue engineering 31 . Increase in cardiomyocyte differentiation potential of embryonic stem cells (ESCs) cultured on PLGA‐collagen nanofibers and MSCs cultured on collagen nanofibers was reported previously by Prabhakaran et al 32 and Joshi et al, 33 respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Results (17)(18)(19)(20). In particular, the role and potential of BM-MSCs in ameliorating MIRI has been previously demonstrated (21)(22)(23). It has been shown that BM-MSCs differentiate into cardiomyocytes under appropriate ex vivo culture conditions (22,23).…”
Section: Discussionmentioning
confidence: 88%
“…In particular, the role and potential of BM-MSCs in ameliorating MIRI has been previously demonstrated (21)(22)(23). It has been shown that BM-MSCs differentiate into cardiomyocytes under appropriate ex vivo culture conditions (22,23). Earlier animal studies reported that BM-MSCs transfusions promoted cardiomyocyte proliferation and angiogenesis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Such matrices can be worked into desired shapes using micromolding, microfluidics, electrostatic droplet extrusion, or bioprinting (Kim et al, 2019). MSC based scaffolds systems have been used for bone and cartilage regeneration (Kim et al, 2019), as well as for the reproduction of blood vessels (Pinnock et al, 2016), cardiac tissue (Rashedi et al, 2017;Ichihara et al, 2018;Joshi et al, 2018), and skeletal muscle (Witt et al, 2017). Optimal tissue replacement efficiency relies on the physical characteristics of the scaffolds (Alakpa et al, 2017;Jeon et al, 2017;Mouser et al, 2018), as each mechanical property can modify the fate of the transplanted cells.…”
Section: Alternative Approaches To Msc Administrationmentioning
confidence: 99%